2020
DOI: 10.1037/men0000224
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation, eating disorder classification, and men’s psychosocial well-being.

Abstract: In a sample of 676 men, we examined (a) the relationship between men's eating disorder (ED) classification (asymptomatic vs. symptomatic/clinical) to theoretically and empirically identified psychosocial correlates (i.e., body image concerns, sociocultural pressures, internalization processes, and depressive symptomatology) and (b) determined the extent to which sexual orientation moderated those relationships. To test our hypotheses, we used the PROCESS v2.16 macro. Consistent with the tenets of objectificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Early research findings suggest that gay adults reported more frequent dieting and greater dietary restraint, more binge eating, less control over their eating behaviors, more purging, and more exercise than heterosexual men [ 56 , 99 , 139 ] and these findings are supported by more contemporary research. Compared to heterosexual men, gay adults reported increased rates of binge eating, disordered eating behaviors, unhealthy weight control behaviors, food addiction, and diagnosed clinical eating disorders, in addition to poorer physical activity ([ 10 , 20 , 27 , 54 , 58 , 67 , 113 , 127 , 137 , 141 , 145 , 146 , 149 , 152 , 159 , 161 , 172 , 173 ]).…”
Section: Eating Disorders and Disordered Eating Behaviors Within Lgbtmentioning
confidence: 99%
“…Early research findings suggest that gay adults reported more frequent dieting and greater dietary restraint, more binge eating, less control over their eating behaviors, more purging, and more exercise than heterosexual men [ 56 , 99 , 139 ] and these findings are supported by more contemporary research. Compared to heterosexual men, gay adults reported increased rates of binge eating, disordered eating behaviors, unhealthy weight control behaviors, food addiction, and diagnosed clinical eating disorders, in addition to poorer physical activity ([ 10 , 20 , 27 , 54 , 58 , 67 , 113 , 127 , 137 , 141 , 145 , 146 , 149 , 152 , 159 , 161 , 172 , 173 ]).…”
Section: Eating Disorders and Disordered Eating Behaviors Within Lgbtmentioning
confidence: 99%
“…In men, sexual orientation might increase the risk of developing an eating disorder, with more men with an ED or ED-related behavior identifying as homosexual compared to the general population [42,43]. Further, independent of being diagnosed with an ED, homosexual men report more psychological distress than heterosexual men and in men with an ED, being homosexual was related to higher ED symptomatology [44]. In women, a review found no significant difference in overall disordered eating due to sexual orientation, but distinct patterns, with homosexual women reporting less restrictive eating behavior and more binge eating [45].…”
Section: Eating Disorders An / Bnmentioning
confidence: 99%